Desenvolvimento e caracterização de gel bioativo à base de fibroína da seda/PLDLA/sinvastatina para impressão 3D - Antunes, Bianca Sabino Leocádio (Universidade Federal de São Carlos, 2022)
Bone Tissue Engineering (BOT) has been growing in recent decades as an effective approach for the treatment of large bone defects. Recently, three-dimensional (3D) printing has emerged as a tool to revolutionize the field of tissue engineering and regenerative medicine along with the release of osteogenic molecules such as Simvastatin (SIM). However, its immobilization in a framework/drug system is still a challenge. Silk fibroin (SF) has been shown to be a promising biomaterial for obtaining scaffolds due to its mechanical properties, controllable biodegradability and adequate cell adhesion/proliferation. The addition of other polymers is studied to control the viscosity of the SF solution, ensuring better quality of the printed structure. The objective of this work is to study the rheological properties of the gel based on SF and PLDLA (poly (L-co-D, L lactic acid)), with SIM, in order to obtain the best composition for 3D scaffold printing, aiming at the bone regeneration. PLDLA syntheses and SF were obtained from silk threads of the bombyx mori species. After this process, the pure SF and PLDLA samples were characterized by DSC, TG and FTIR. Then, SF-PLDLA solutions were prepared in formic acid, varying the concentrations of SF and PLDLA where they were subjected to rheological tests in permanent and oscillatory regimes. The chosen formulations were then submitted to the 3D printing process, obtaining structured scaffolds with pores, where the formulation of FS 15.0% with the addition of PLDLA 7.0%, resulted in the construction of a more reliable scaffold to the original design, compared to to the SF 15.0%/PLDLA 3.0% and SF 15.0%/PLDLA 10.0% formulations, presenting more evident pores and meeting the criteria of pseudoplasticity, viscoelasticity and thixotropy, important requirements for a solution to be suitable for 3D printing. The rheological assays showed that the addition of SIM at concentrations of 0.1%, 0.25%, 0.5%, 1.0% and 2.0% did not significantly alter the pseudoplastic, viscoelastic and thixotropic behavior of the gel SF 15.0%/PLDLA 7.0%.
Development and characterization of a bioactive gel based on silk fibroin/PLDLA/simvastatin for 3D printing
Keywords: Reologia; Hidrogel; Impressão 3D; PLDLA; Fibroína da Seda; Sinvastatina; Rheology; Hydrogel; 3D printing; Silk Fibroin; Simvastatin; ENGENHARIAS::ENGENHARIA BIOMEDICA::BIOENGENHARIA::MODELAGEM DE SISTEMAS BIOLOGICOS; ENGENHARIAS::ENGENHARIA BIOMEDICA::BIOENGENHARIA; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS::POLIMEROS, APLICACOES